Comparative Efficacy of Novel Insecticides Against Cotton Whitefly (Bemisia Tabacci L.) For Sustainable Cotton Production (Journal of Agriculture and Biology, 2025)
Whitefly (Bemisia tabacci) is a major pest of cotton worldwide, causing significant economic losses by reducing crop yield and transmitting plant viruses. In Pakistan, whitefly infestations have severely impacted cotton production, leading to decreased fiber quality and lower yields. Effective pest management techniques are required to maintain the crop. Whitefly is a big problem in cotton production because it creates physiological stress and affects yield. In this study, the effectiveness of various chemical treatments on morphological and biochemical characters of cotton is assessed. Spirotetramite was found least effective, whereas Pymetrozine was the most effective and significantly decreased whitefly population. In control the increasing trend of whitefly population growth was observed from third to the fourteenth day after application (DAA). An indicator of oxidative stress, hydrogen peroxide (H2O₂), rose in control plants but fell in chemically treated plants; the greatest decrease was seen with pyriprofen, suggesting improved tolerance. Total antioxidant activity (TAO) increased in all treatments, highlighting the biochemical defense response. Chlorophyll and carotenoid levels declined from the 3rd to the 14th DAA, reflecting pigment degradation due to oxidative stress. These findings suggest that chemical treatments not only reduce whitefly populations but also modulate biochemical pathways in cotton to mitigate oxidative damage. Pymetrozine and Pyriproxyfen were identified as the most effective treatments for whitefly management and stress alleviation.